2000
DOI: 10.1002/1096-8628(20001204)96:6<823::aid-ajmg26>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Association of a haplotype for tumor necrosis factor in siblings with late-onset Alzheimer disease: The NIMH Alzheimer disease genetics initiative

Abstract: Tumor necrosis factor (TNF), a proinflammatory cytokine, may be involved in the pathogenesis of Alzheimer disease (AD) based on observations that senile plaques have been found to upregulate proinflammatory cytokines. Additionally, nonsteroidal anti-inflammatory drugs have been found to delay and prevent the onset of AD. A collaborative genome-wide scan for AD genes in 266 late-onset families implicated a 20 centimorgan region at chromosome 6p21.3 that includes the TNF gene. Three TNF polymorphisms, a -308 TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
2
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 87 publications
2
71
2
2
Order By: Relevance
“…11 Padovani et al 12 have shown that this polymorphism may increase the risk of myocardial infarction (MI) in obese subjects. Moreover, Collins et al 13 have found a significant association between Alzheimer's disease (AD) and a haplotype that included the À308 polymorphism and the TNF-a À238G/A polymorphism, in addition to a significant association involving solely the À238 polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…11 Padovani et al 12 have shown that this polymorphism may increase the risk of myocardial infarction (MI) in obese subjects. Moreover, Collins et al 13 have found a significant association between Alzheimer's disease (AD) and a haplotype that included the À308 polymorphism and the TNF-a À238G/A polymorphism, in addition to a significant association involving solely the À238 polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Tumour necrosis factor alpha (TNF-α) is a critical mediator of host defence against infection. Polymorphisms in the gene encoding TNF-α might determine a strong cell-mediated immune response or a weak or absent cellular response, which reflects the genetic variability in cytokine production (Refs 352,353 61,358,359,360,361,362).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Elevated serum levels of pro-infl ammatory cytokines (Paganelli et al 2002), in particular TNF (Fillit et al 1991;Collins et al 2000;Alvarez et al 2007;Tan et al 2007), have been detected in patients with severe AD.…”
Section: Tnf In Alzheimer's Diseasementioning
confidence: 99%
“…In support of this idea, the bacterial endotoxin lipopolysaccharide (LPS), a potent trigger of infl ammation that elicits production of TNF and many other cytokines (Flick and Gifford 1986), can accelerate the appearance and severity of AD pathology in several animal models of AD (Qiao et al 2001;Sheng et al 2003), including the triple-transgenic (3 × TgAD) mouse (Kitazawa et al 2005), in which upregulation of TNF mRNA precedes the appearance of amyloid-associated pathology (Janelsins et al 2005) and correlates with cognitive defi cits (Billings et al 2005). We also review the evidence implicating TNF signaling in AD pathology and discuss how TNF-dependent processes may contribute to cognitive dysfunction and accelerated progression of AD (Fillit et al 1991;Collins et al 2000;Paganelli et al 2002;Ma et al 2004;Tobinick et al 2006;Alvarez et al 2007;Tan et al 2007). We conclude by reviewing the observations that provide compelling rationale to investigate the extent to which new therapeutic approaches that selectively target the TNF pathway modify progression of neuropathology in preclinical models of AD as well as the promising fi ndings with the use of nonsteroidal anti-infl ammatory drugs (NSAIDs) and recent clinical trials with Aβ immunotherapy.…”
Section: Introductionmentioning
confidence: 99%